2010
DOI: 10.1002/ctpp.201010149
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution of Plasma Parameters in DC‐Energized Hollow Cathode Plasma Jet

Abstract: DC energized hollow cathode plasma jet system was examined by radially movable Langmuir probe. Radial distribution of electron concentration, plasma and floating potentials and mean electron energy were obtained from measured probe characteristics at the distance 17 mm downstream of the hollow cathode -nozzle. The radial dependence of plasma parameters was measured for distances from the system axis 0-120 mm in the discharge containing Ar and O2. Two scenarios were used: addition of O2 into the nozzle and into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 21 publications
6
3
0
Order By: Relevance
“…Furthermore this research extends our previous work carried out under higher pressures reported in [17,18]. Furthermore this research extends our previous work carried out under higher pressures reported in [17,18].…”
Section: Langmuir Probe Diagnosticssupporting
confidence: 89%
See 3 more Smart Citations
“…Furthermore this research extends our previous work carried out under higher pressures reported in [17,18]. Furthermore this research extends our previous work carried out under higher pressures reported in [17,18].…”
Section: Langmuir Probe Diagnosticssupporting
confidence: 89%
“…Furthermore this research extends our previous work carried out under higher pressures reported in [17,18]. While as it was presented in [17] in the pressure range of tens of Pa the electron density decreases with the pressure due to faster recombination the dependence at low pressures seem to be inverse. From the measured Langmuir probe characteristics the floating and plasma potential, electron density, electron temperature and electron energy probability functions were evaluated.…”
Section: Langmuir Probe Diagnosticssupporting
confidence: 89%
See 2 more Smart Citations
“…In such situation, the cathode geometry configuration is one of the possibilities that can improve the plasma parameters in terms of self-bias voltage (V dc ), electron density (n e ) and electron temperature (T e ), etc. [12][13][14]. In this sense, hollow and multi-hollow (H and MH) cathodes were proposed to be utilized as a light source [15], active media for gas lasers [16], sources of electrons [17], or for thin films deposition and large area surface treatment [18][19][20], and recently for the treatment of nanoparticles, plasma polymerization and nanocomposite fabrication [21].…”
Section: Introductionmentioning
confidence: 99%